Effects of MetAP2 inhibition on hyperphagia and body weight in Prader–Willi syndrome: A randomized, double‐blind, placebo‐controlled trial. Issue 12 (13th July 2017) - McCandless, Shawn E.; Yanovski, Jack A.; Miller, Jennifer; Fu, Cary; Bird, Lynne M.; Salehi, Parisa; Chan, Christine L.; Stafford, Diane; Abuzzahab, M. Jennifer; Viskochil, David; Barlow, Sarah E.; Angulo, Moris; et al.
Abstract : Aims: There are no treatments for the extreme hyperphagia and obesity in Prader–Willi syndrome (PWS). The bestPWS clinical trial assessed the efficacy, safety and tolerability of the methionine aminopeptidase 2 (MetAP2) inhibitor, beloranib. Materials and Methods: Participants with PWS (12‐65 years old) were randomly assigned (1:1:1) to biweekly placebo, 1.8 mg beloranib or 2.4 mg beloranib injection for 26 weeks at 15 US sites. Co‐primary endpoints were the changes in hyperphagia [measured by Hyperphagia Questionnaire for Clinical Trials (HQ‐CT); possible score 0‐36] and weight by intention‐to‐treat. ClinicalTrials.gov registration: NCT02179151. Results: One‐hundred and seven participants were included in the intention‐to‐treat analysis: placebo ( n = 34); 1.8 mg beloranib ( n = 36); or 2.4 mg beloranib ( n = 37). Improvement (reduction) in HQ‐CT total score was greater in the 1.8 mg (mean difference −6.3, 95% CI −9.6 to −3.0; P = .0003) and 2.4 mg beloranib groups (−7.0, 95% CI −10.5 to −3.6; P = .0001) vs placebo. Compared with placebo, weight change was greater with 1.8 mg (mean difference − 8.2%, 95% CI −10.8 to −5.6; P < .0001) and 2.4 mg beloranib (−9.5%, 95% CI −12.1 to −6.8; P < .0001). Injection site bruising was the most frequent adverse event with beloranib. Dosing was stopped early due to an imbalance in venous thrombotic events in beloranib‐treated participants (2 fatal events of pulmonary embolism and 2 events of deep vein thrombosis) compared with placebo. Conclusions: MetAP2 inhibition with beloranib produced statistically significant and clinically meaningful improvements in hyperphagia‐related behaviours and weight loss in participants with PWS. Although investigation of beloranib has ceased, inhibition of MetAP2 is a novel mechanism for treating hyperphagia and obesity.